Política de integração curricular das TIC em Portugal - Elisabete Cruz; Fernando Albuquerque Costa; Sandra Fradão (EccoS – Revista Científica)
In this paper we make use of the work that we have recently developed in the context of the project "Learning Outcomes" hosted by the Portuguese Ministry of Education in 2010. In order to explain and share the work done regarding ICT, this paper presents and discusses the rationale that supported an ICT Learning Outcomes Framework based on four main competence domains. After clarifying the concept of teaching and evaluation strategies used in the project, we conclude that we need to continue to broaden and deepen our knowledge regarding the challenges and demands of this proposal because, in contrast to a mono-disciplinary approach, it means the school culture must change into a cooperative culture based on partnerships formed by everyone operating within school.